Radiotherapy- or Radical Surgery–Induced Female Sexual Morbidity in Stages IB and II Cervical Cancer. Issue 4 (1st May 2014) - Harding, Yuko; Ooyama, Takuma; Nakamoto, Tomoko; Wakayama, Akihiko; Kudaka, Wataru; Inamine, Morihiko; Nagai, Yutaka; Ueda, Shinichiro; Aoki, Yoichi
Abstract : Objective: The objective of this study was to evaluate the sexual function in cervical cancer survivors after radiotherapy (RT) or radical surgery (RS). Methods: This was an observational and cross-sectional study. The Female Sexual Function Index (FSFI) self-reported questionnaires were distributed to 175 patients after RT (RT group) or RS (RS group) and 521 healthy women (control) between 2011 and 2012. Sexual functions were compared among these 3 groups. Results: Eligible 92 patients (46 in RT group, 46 in RS group) and 148 control subjects were included for analysis. There was a significant difference in median (range) FSFI total score of 5.5 (3.6–34.7) in the RT group, 18.9 (3.4–31.2) in the RS group, and 22.1 (2–34.2) in the control group ( P < 0.001). The median FSFI total score in the RT group was significantly lower than that in the control group ( P < 0.001). Six sexual domains (desire, arousal, lubrication, orgasm, satisfaction, pain) were all significantly affected in the RT group, and no significant differences, except pain, were observed in the RS group as compared with the control group. Conclusions: Interventions involving counseling and rehabilitation for female sexual function should be provided in cervical cancer survivors, especially after RT.